Multidimensional Poverty, Gender, and Forced Displacement : A Multi-Country, Intrahousehold Analysis in Sub-Saharan Africa - Admasu, Yeshwas; Alkire, Sabina; Scharlin-Pettee, Sophie (World Bank, Washington, DC, 2021)
This paper examines multidimensional poverty among forcibly displaced populations, using a gendered lens. Although past studies have explored poverty in forcibly displaced contexts, and others have looked at the relationship between multidimensional poverty and gender, none has brought together these three issues—multidimensional poverty, forcibly displaced persons, and gender. A tailored measure of multidimensional poverty is developed and applied for refugees and internally displaced populations in five Sub-Saharan African settings substantially affected by forced displacement—Ethiopia, Nigeria, Somalia, South Sudan, and Sudan. The gendered analysis builds on prior analysis of the Multidimensional Poverty Index (MPI) by examining individual-level deprivations of women and men in forcibly displaced households and host communities, as well as synthesizing intrahousehold dynamics of multidimensional poverty in forcibly displaced communities. The results provide insights into the educational constraints of boys and girls living in forcibly displaced households, the labor market inequalities experienced by men and women in these communities, and their differential access to legal documentation and employment as part and parcel of the forced displacement experience.